2012
DOI: 10.1073/pnas.1120195109
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule antagonist reveals seizure-induced mediation of neuronal injury by prostaglandin E2 receptor subtype EP2

Abstract: With interest waning in the use of cyclooxygenase-2 (COX-2) inhibitors for inflammatory disease, prostaglandin receptors provide alternative targets for the treatment of COX-2-mediated pathological conditions in both the periphery and the central nervous system. Activation of prostaglandin E2 receptor (PGE 2 ) subtype EP2 promotes inflammation and is just beginning to be explored as a therapeutic target. To better understand physiological and pathological functions of the prostaglandin EP2 receptor, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
194
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(205 citation statements)
references
References 30 publications
8
194
1
1
Order By: Relevance
“…8 In contrast, EP2 receptor signaling protects cultured neurons under various conditions through the cAMP/PKA or cAMP/Epac pathway [9][10][11][12] and regulates microglial activation and function in vitro. [13][14][15][16] These findings reflect cell-specific differences in EP2 signaling. In vivo work has shown that the EP2 receptor has beneficial effects in models of ischemic stroke 12,17,18 but detrimental effects in models of Alzheimer's disease, 19,20 Parkinson's disease, 21 and amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 86%
“…8 In contrast, EP2 receptor signaling protects cultured neurons under various conditions through the cAMP/PKA or cAMP/Epac pathway [9][10][11][12] and regulates microglial activation and function in vitro. [13][14][15][16] These findings reflect cell-specific differences in EP2 signaling. In vivo work has shown that the EP2 receptor has beneficial effects in models of ischemic stroke 12,17,18 but detrimental effects in models of Alzheimer's disease, 19,20 Parkinson's disease, 21 and amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 86%
“…Likewise, 100 nM or 0.3 M TG4-155 produced a parallel shift to the right in the concentration-response curves of both agonists with the magnitude of the shift being similar in both resting and activated state conditions. The estimated Schild K B is 14 nM against butaprost and 10 nM against PGE 2 , which is about a 5-fold lower potency than that measured in C6G cells overexpressing human EP2 receptors (28). These data together with pharmacological results described above demonstrate that PGE2 and butaprost up to at least 1 M act entirely on EP2 receptors in both resting and activated rat microglia, that the weaker action of butaprost on EP3 receptors (38) does not come into play under our conditions, and that the only source of cAMP in PGE 2 -stimulated microglia is EP2.…”
Section: Ep2 Activation Modulates Expression Of Inflammatory Mediatormentioning
confidence: 96%
“…The novel EP2 potentiator TG3-95-1 (referred to as compound 1 in Ref. 27) and EP2 antagonist TG4-155 were synthesized in our laboratory (27)(28)(29). All plasticware and reagents were endotoxin-free.…”
Section: Methodsmentioning
confidence: 99%
“…This effect was associated with reduction of neuronal cell loss, and inhibition of mossy fibers sprouting. Jiang et al [146] also found that pharmacological inhibition of PGE2 receptor subtype EP2 is neuroprotective in pilocarpine model of SE.…”
Section: Immunity and Anti-inflammatory Therapies In Epilepsymentioning
confidence: 99%